Black shoes policy : parents' perceptions towards itsimplementation / Afifah Hanani Rosdi ... [et al.] - Rosdi, Afifah Hanani; Idris, Izaida Raihanah; Fudzil, Safinah; Syed Othman, Sharifah Asilah; Saari, Izni Syamsina; Atan, Mohd Amirul (Universiti Teknologi MARA, Perak, 2019)
The purposes of the study are to gain a deeper understanding on parents' perceptions and to investigate the correlation between important factors (school climates, behaviour, economy, hygiene and effectiveness) and perception on the wearing of black shoes in Malaysian schools. The data were collected from 318 parents from urban, sub-urban and rural areas from all over the state of Melaka, Malaysia who were randomly selected using cluster sampling. The results were analysed based on demographic characteristics which were gender, place of origin, race, religion, occupation, age, higher education level and monthly income. The findings revealed that a majority of parents who had children going to school accepted the black shoes policy. They agreed with the abolishment of the previously implemented white shoes policy due to important factors such as school climate, behaviour, economy, hygiene and effectiveness. Based on the findings, the researchers found out that each important factor (school climate, behaviour, effectiveness, hygiene, and economy) had a strong significant correlation with the perception of parents as they affected the decision criteria of the parents. All variables resulted with p-value < 0.001.